Aspergillus sp. For Indigosol Blue and Remazol Brilliant Blue R Decolorization - Fitria Ayudi Ulfimaturahmah; Ratna Stia Dewi; Ajeng Arum Sari (BioEksakta : Jurnal Ilmiah Biologi Unsoed, 2020)
Synthetic dyes are artificial dyes manufactured by Industry and commonly used for the textile industry. These dyes had potentially caused an environmental problem. Many types of dyes are recalcitrant and have toxic properties for living organisms. It can be removed by decolorization method, especially a biological decolorization by fungi. Fungi were chosen due to the ability to degrade toxic components. Aspergillus sp. is the fungi which commonly used for dye decolorization. It might be caused that Aspergillus sp. is one type of fungi lived in the textile waste and expected not to die in the dye decolorization treatment. The purpose of this research was to investigate the ability of the mycelia pellets of Aspergillus sp to decolorized Indigosol Blue dye and Remazol Brilliant Blue R (RBBR) dye. This research showed that mycelial pellets of Aspergillus sp. had high activity of decolorization of Indigosol Blue dye up to 85.37% and RBBR dye up to 80.21% and caused low pH value after 24 hour incubation time compared to the control solution.